tert-Butoxide-Mediated Protodeformylative Decarbonylation of α-Quaternary Homobenzaldehydes - Stokes, Benjamin J.; Cai, Xiao; Amsbaugh, Ritter V.; Drake, Lauren J.; Kotamraju, Ravi M. A.; Licauco, Nicholas Javier C. (SynOpen, 2024)
tert-Butoxide mediates the Haller–Bauer-type (protodeformylative) decarbonylation of readily accessed α-quaternary homobenzaldehydes and related compounds at room temperature, generating cumene products. Both geminal dialkyl and geminal diaryl substituents are tolerated. gem-Dimethyls are sufficient for decarbonylation of polycyclic arenyl substrates whereas monocyclic aromatic homobenzaldehydes require cyclic gem-dialkyls or gem-diaryls for significant decarbonylation.
Keywords: decarbonylation; C–C bond cleavage; protodeformylation; Haller–Bauer reaction; tert-butoxide; benzylic anion; cumenes